Development and psychometric properties of a short version of the Patient Continuity of Care Questionnaire - Emma Safstrom; Kristofer Arestedt; Heather D. Hadjistavropoulos; Maria Liljeroos; Lena Nordgren; Tiny Jaarsma; Anna Stromberg (Wiley, 2023)
Abstract Introduction Hospitalization due to cardiac conditions is increasing worldwide, and follow‐up after hospitalization usually occurs in a different healthcare setting than the one providing treatment during hospitalization. This leads to a risk of fragmented care and increases the need for coordination and continuity of care after hospitalization. Furthermore, international reports highlight the importance of improving continuity of care and state that it is an essential indicator of the quality of care. Patients' perceptions of continuity of care can be evaluated using the Patient Continuity of Care Questionnaire (PCCQ). However, the original version is extensive and may prove burdensome to complete; therefore, we aimed to develop and evaluate a short version of the PCCQ. Methods This was a psychometric validation study. Content validity was evaluated among user groups, including patients (n = 7), healthcare personnel (n = 15), and researchers (n = 7). Based on the results of the content validity and conceptual discussions among the authors, 12 items were included in the short version. Data from patients were collected using a consecutive sampling procedure involving patients 6 weeks after hospitalization due to cardiac conditions. Rasch analysis was used to evaluate the psychometric properties of the short version of the PCCQ. Results A total of 1000 patients were included [mean age 72 (SD = 10), 66% males]. The PCCQ‐12 presented a satisfactory overall model fit and a person separation index of 0.79 (Cronbach's α: .91, ordinal α: .94). However, three items presented individual item misfits. No evidence of multidimensionality was found, meaning that a total score can be calculated. A total of four items presented evidence of response dependence but, according to the analysis, this did not seem to affect the measurement properties or reliability of the PCCQ‐12. We found that the first two response options were disordered in all items. However, the reliability remained the same when these response options were amended. In future research, the benefits of the four response options could be evaluated. Conclusion The PCCQ‐12 has sound psychometric properties and is ready to be used in clinical and research settings to measure patients' perceptions of continuity of care after hospitalization. Patient or Public Contribution Patients, healthcare personnel and researchers were involved in the study because they were invited to select items relevant to the short version of the questionnaire.